To correctly solve the equation \( 2x - 5 = 3(4x + 5) \) and order the steps accordingly, let's review the correct sequence of operations and clarify the terminology used.
-
Start with the original equation: \[ 2x - 5 = 3(4x + 5) \]
-
Step 1: Distributive Property
Apply the distributive property on the right side: \[ 2x - 5 = 12x + 15 \] -
Step 2: Addition of Equality Property
Add 5 to both sides to isolate terms involving \(x\): \[ 2x = 12x + 20 \] -
Step 3: Subtraction of Similar Terms
Subtract \(12x\) from both sides: \[ 2x - 12x = 20 \] \[ -10x = 20 \] -
Step 4: Division of Equality Property
Divide both sides by -10: \[ x = -\frac{20}{10} = -2 \]
So the ordered steps to correctly solve the equation \( 2x - 5 = 3(4x + 5) \) are:
- Distributive Property: \( 2x - 5 = 12x + 15 \)
- Addition of Equality Property: \( 2x = 12x + 20 \)
- Subtraction of Similar Terms: \( -10x = 20 \)
- Division of Equality Property: \( x = -2 \)
(Note: The steps you provided had some errors and need adjusting for both the operations and the results.)